Sigit Raditya's Political Marketing in the 2024 Legislative Election Campaign in West VI Electoral District - Zazuli, Mohamad Zanuar Rafildy; Solihah, Ratnia; Djuyandi, Yusa (GoAcademica Research & Publishing, 2025)
In the 2024 legislative campaign, Sigit Raditya competed as a legislative candidate in one of the highly competitive electoral districts, the West Java VI Electoral District. Sigit Raditya lost in competing in the electoral district. This study uses a qualitative design with primary data through interviews with Sigit Raditya and the campaign team in Bekasi and Depok. The analysis was carried out using Nursal's political marketing framework which divides the focus of political marketing into three strategies, namely push, pull, and pass marketing. This study shows findings that in the political marketing that has been implemented by the Sigit Raditya campaign team, all three approaches have been contextually applied in the campaign in Bekasi and Depok. As a newcomer, formation and strengthening through an emotional approach with face-to-face practices are carried out in the push marketing strategy. However, this strategy is not optimal due to inadequate volunteer capacity and Sigit Raditya's absence from several face-to-face visit schedules which reduce his exposure to the grassroots. Then exposure to attract voters through visual media in a combination of digital (social media) and conventional (billboards, brochures) has also been implemented, but there are some inconsistencies in the visuals and aesthetics offered on social media and the distribution of props is uneven. While marketing using the pass marketing approach has attracted several public figures to strengthen support at the grassroots level, this strategy can still require encouragement from the involvement of public figures or influencers who work actively to market Sigit Raditya so that the reach of messages and exposure can increase and expand.